Remarks on Recent Uses of Greek and Latin Words in the Field of Zoological Nomenclature (Minerva, 2017)
The article provides a concise but representative panorama of some recent tendencies in zoological nomenclature, especially in terms regarding the vertebrates. It focuses both in scientific Neolatin (the original vehicle for this terminology) and in modern languages, with particular attention to Spanish. The paper does not consider the scientist’s point of view, but that of a linguist interested in Greek and Latin word constituents in European languages. Both of them, from a morphological and semantic standpoint, often behave in a quite different way in comparison with ancient Greek and Latin. This is the reason for which they deserve, as it is argued, the careful attention of the classical scholar.
Keywords: greek an latin word constituents; scientific Neo-Latin; zoological nomenclature